Enteropathogens in children less than 5 years of age with acute diarrhea: a 5-year surveillance study in the Southeast Coast of China. Issue 1 (December 2016) - Zheng, Shufa; Yu, Fei; Chen, Xiao; Cui, Dawei; Cheng, Yongzhang; Xie, Guoliang; Yang, Xianzhi; Han, Dongsheng; Wang, Yiyin; Zhang, Wen; Chen, Yu
Abstract Background Diarrhea is the second most common cause of death among children less than 5 years of age worldwide. The etiological agents of diarrhea in the southeast coastal area of China were studied from July 2009 to December 2014. Methods A total of the 2318 patients were enrolled in this study and examined for the presence of viruses, bacteria, and parasites. Multiplex real-time PCR was used for the detection of diarrheagenicEscherichia.coli (DEC). DEC strains were tested for susceptibility to a panel of 20 antibiotics using the Kirby-Bauer disc-diffusion method. Results Of the 2318 children with diarrhea, 962 (41.5 %) were positive for at least one pathogen. Rotavirus, human calicivirus (HucV), and DEC were predominant, with detection rates of 19.1 % (443), 17.7 % (411), and 7.6 % (177), respectively. The prevalences of various pathogens in patients of different ages and in different seasons were not the same. The resistance rates of 177 strains of DEC to ampicillin, tetracycline, and cefazolin were 93.2 %, 60.0 %, and 57.7 %, respectively. Conclusions Rotavirus, HucV, and DEC were the main pathogens associated with diarrhea in Zhejiang, China. DEC possessed high levels of antibiotic resistance. Increased monitoring of etiological agents of diarrhea is necessary.